2020
DOI: 10.1088/1742-6596/1521/2/022025
|View full text |Cite
|
Sign up to set email alerts
|

The effect of project based learning-STEM on problem solving skills for students in the topic of electromagnetic induction

Abstract: Problem solving skills is one of six topical areas of physics education research, whereas the research about implementation of Project Based Learning-Science Technology Engineering and Mathematics (PjBL-STEM) to enhance students’ problem solving skills is still lacking. This research purposed to reveal the impact of PjBL-STEM on students’ problem solving skills in the topic of Electromagnetic Induction with a quasi experiment non-equivalent group design. Grade XII students of Senior High School 2 Pasuruan Indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
0
17
1
1
Order By: Relevance
“…The effect of STEM education on problem solving skills was also examined and it was concluded that STEM education did not contribute to the problem solving skills of the students. Unlike the results of this study, Parno et al, (2020) found that Project Based Learning-Science Technology Engineering and Mathematics (PjBL-STEM) application increased students' problem solving skills. Similarly, Yamak et al, (2014) reported that STEM education improved students' scientific process skills such as identifying and defining a problem, researching, questioning, and solving problems and that the designs made by students in the classroom helped them develop a positive attitude towards science classes.…”
Section: Discussioncontrasting
confidence: 99%
“…The effect of STEM education on problem solving skills was also examined and it was concluded that STEM education did not contribute to the problem solving skills of the students. Unlike the results of this study, Parno et al, (2020) found that Project Based Learning-Science Technology Engineering and Mathematics (PjBL-STEM) application increased students' problem solving skills. Similarly, Yamak et al, (2014) reported that STEM education improved students' scientific process skills such as identifying and defining a problem, researching, questioning, and solving problems and that the designs made by students in the classroom helped them develop a positive attitude towards science classes.…”
Section: Discussioncontrasting
confidence: 99%
“…Based on the results obtained regarding the cognitive and psychomotor domains in this study, it was known that there was an increase from cycle I to cycle II. Research conducted by Parno et al (2020) also showed that this application was able to improve the skills of vocational students. If we take a look at the learning outcomes of students in the cognitive domain, there was an increase of 8.3 percent between learning outcomes in pretreatment and learning outcomes in cycle II and there was an increase of 8.4 percent from learning outcomes in cycle I with learning outcomes in the second cycle.…”
Section: The Results Of Psychomotor Aspect In the Second Cyclementioning
confidence: 89%
“…The Blue Cluster states that PjBL-STEM research relates to gender, career, and selfefficacy (Hasbullah et al, 2020). Green cluster explained that in PjBL-STEM research that has been conducted by the researchers two there are related to the problems faced during learning, the effects of learning PjBL-STEM include improving the ability of creative thinking and learning in daily life (Parno, Yuliati, Munfaridah, et al, 2020), and instruments used in the study in the form of questionnaires and tests. In (Figure 9a), Physics learning with PjBL-STEM affects gender and race.…”
Section: Methodsmentioning
confidence: 99%